Temporomandıbular Joınt Dısorders And Treatment Approaches - Cenk Ahmet Akcan; İlken Kocadereli (Galenos Yayinevi, 2003)
In this article temporomandibular joint disorders and various treatment approaches currently in use will be evaluated.